Chemical composition of essential oils from citrus microcarpa (variegated). - Aminudin, Nurul Iman; Md Isa, Nur Aliea Afief; Jani, Nor Akmalazura; Jamil, Mailina; Md Ali, Norazah (2019)
The chemical composition of Citrus microcarpa (variegated) or commonly known as ‘limau kasturi batik’ were determined in this study. Essential oils of the leaves and peels of C. microcarpa (variegated) were extracted by using hydrodistillation technique and analyzed by capillary gas chromatography-mass spectrometry (GC-MS). A total of 32 compounds accounting for 91.70% of the leaves oil composition and 14 compounds accounting for 90.54% of the peels oil composition were detected. The main constituent in the leaves oil are germacrene D (17.85%), β-eudesmol (17.41%), hedycaryol (7.67%), germacrene B (5.07%) and β-caryophyllene (4.91%). Meanhile, limonene (76.6%), β-eudesmol (3.07%), -terpineol (2.59%) and γ-eudesmol (2.07%) are the major components found in the peels oil.